Information Technology, Gender Economic Inclusion and Environment Sustainability in Sub-Sahara Africa - Cheikh T. Ndour; Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
Purpose - This study examines the relevance of information and communication technologies in the effect of gender economic inclusion on environmental sustainability. Design/methodology/approach - The focus is on a panel of 42 sub-Saharan African countries over the period 2005-2020. The empirical evidence is based on generalized method of moments. The environmental sustainability indicator used is CO2 emissions per capita. Two indicators of women's economic inclusion are considered: women's labour force participation and women's unemployment. The chosen ICT indicators are mobile phone penetration, internet penetration and fixed broadband subscriptions. Findings - The results show that: (i) fixed broadband subscriptions represent the most relevant ICT moderator of gender economic inclusion for an effect on CO2 emissions; (ii) negative net effects are apparent for the most part with fixed broadband subscriptions (iii) both positive ICT thresholds (i.e., critical levels for complementary policies) and negative ICT thresholds (i.e., minimum ICT levels for negative net effects) are provided; (iv) ICT synergy effects are apparent for female unemployment, but not for female employment. In general, the joint effect of ICTs or their synergies and economic inclusion should be a concern for policymakers in order to better ensure sustainable development. Moreover, the relevant ICT policy thresholds and mobile phone threshold for complementary policy are essential in promoting a green economy. Originality/value -The study complements the extant literature by assessing linkages between information technology, gender economic inclusion and environmental sustainability.
Keywords: C52; O38; O40; O55; P37; 330; ICT; Gender inclusion; Environment sustainability; Sub-Saharan Africa